Feasibility of conducting a randomized controlled trial comparing family‐based treatment via videoconferencing and online guided self‐help family‐based treatment for adolescent anorexia nervosa. Issue 11 (22nd September 2021) - Lock, James; Couturier, Jennifer; Matheson, Brittany E.; Datta, Nandini; Citron, Kyra; Sami, Sadaf; Welch, Hannah; Webb, Cheryl; Doxtdator, Kyrsten; John‐Carson, Natalie
Abstract: Objective: This report describes the feasibility, acceptability, and outcomes from a pilot randomized clinical trial (RCT) comparing an online guided self‐help program version of family‐based treatment (GSH‐FBT) for parents with a child with DSM‐5 anorexia nervosa (AN) to FBT delivered via videoconferencing (FBT‐V). Method: Between August 2019 and October 2020, 40 adolescents ages 12–18 years with DSM‐5 AN and their families were recruited at two sites and randomized to either twelve 20‐min guided sessions of GSH‐FBT for parents or fifteen 60‐min sessions of FBT‐V for the entire family. Recruitment, retention, and acceptability of treatment were the primary outcomes. Secondary outcomes were changes in weight, eating disorder examination (EDE), parental self‐efficacy, weight remission, full remission, and outcome efficiency (therapist time needed to achieve treatment outcomes). Results: Descriptive data are reported. Recruitment and retention rates are similar to RCTs using in‐person treatments. Both treatments received similar acceptability rates. Medium and large effect sizes (ES) related to improvements in weight, EDE, parental self‐efficacy, and remission were achieved in both treatments and were maintained at a 3‐month follow‐up. Clinical outcomes between groups were associated with a small ES. Differences in efficiency (outcome/therapist time) were associated with a large ES difference favoring GSH‐FBT. Discussion: These data support the feasibility of conducting an adequately powered RCT comparing online GSH‐FBT to FBT‐V to determine which approach is more efficient in achieving improvements in clinical outcomes in adolescents with AN.